PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV C SD NEGERI I67 PEKANBARU - Santi Sarli; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the students achievement of social fourth graderes studies still low with an average value of 75,60 and minimum completeness criteria (KKM) social studies is 81. Between students, amounting to 40 people only 12 students who achieve classical KKM with 30%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of science studies class IVc at SDN 167 Pekanbaru with implementation  model problem instruction. Formulation of the problem : Is the implementation  of problem instruction can improve students achievement of social studies at class IVc SDN 167 Pekanbaru. The research was conducted month April. Subjects were students of SDN 167 Pekanbaru, totaling 40 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action  an improve in base score cycle with the average being 75,60. In the first cycle improve an average of 77,50 with increase big as 84,12. Activities of the teacher in the learning process in cycle of 1with increase big as and the second meeting improve to 71,44% and the second meeting improve 82,14%. Cycle II first meeting and the second meeting improve 85,71% to 92,85%. In the third cycle of the first meeting and the second meeting improve 73,07% to 76,92%. Results of data analysis of students activities in the first cycle with the first meeting of an average of 85,76% and a second meeting improve to 90,38% in the class IVc at SDN 167 Pekanbaru that the implementation of problem inkuiri can improve the student achievement of science studiesat fourth graderes SDN 167 Pekanbaru. Key Words: Model Problem instruction, learning outcames IPA